SOSIALISASI ANTI-BULLYING SEBAGAI IMPLEMENTASI NILAI-NILAI PANCASILA DI SMAN 9 PEKANBARU - Ginna Arvi Nanda; Annisa Mutia; Syakirah Permata Auliya; Rado Justeza; Ilham Hudi; Naila Awalia Antoni (Jurnal Padamu Negeri, 2026)
Bullying remains a prevalent problem in the school environment and has negative impacts on students’ psychological, social, and academic development. This article aims to describe the implementation and impact of anti-bullying socialization activities as an application of Pancasila values at SMAN 9 Pekanbaru. The method employed was descriptive qualitative, involving student interviews and the delivery of material through educational presentations. The activity was conducted on November 27, 2025, by students of Universitas Muhammadiyah Riau. The results indicate that prior to the socialization, students’ understanding of bullying was largely limited to physical and verbal acts. After the activity, students were able to recognize various forms of bullying, understand its impacts, and appreciate the importance of empathy and tolerance. This activity contributed to the creation of a safe, inclusive school environment aligned with the values of Pancasila.